An energy aware enhanced AODV routing protocol in MANET. (1st January 2013) - Savitha, K.K.; Chandrasekar, C.
As the growth of multimedia communication in mobile ad hoc networks (MANETs), every node needs to conserve its power since most nodes are powered by a battery source. Mobile ad hoc networking is a challenging task due to the lack of resources in the network as well as the frequent changes in network topology. Although lots of research has been done on supporting QoS in the internet and other networks, but they are not suitable for mobile ad hoc networks and still QoS support for such networks remains an open problem. In this paper, we propose that the enhanced ad hoc on-demand distance vector (AODV) routing protocol which is modified to improve the networks lifetime in mobile ad hoc network (MANET). The new scheme has been proposed for achieving QoS in terms of packet delivery, better power management and stable routes. The proposed scheme has been incorporated using AODV protocol.